Disaster management : a guide to issues management and crisis comunication - Skinner, J. C. (J. Chris); Mersham, G. M. (Gary Malcolm), 1949- (Oxford ; New York : Oxford University Press, 2002)
This book sets out to identify the common features and mechanisms needed to deal with a wide variety of potential disaster.
Includes bibliographical reference (p. 177-178) and index.
aug 30/05/13
Loans
Keywords: Emergency management; Crisis management; Disaster relief -- Handbooks, manuals etc